The relationship between common risk factors and the pathology of pressure ulcer development: a systematic review. (2nd March 2020) - Blackburn, Joanna; Ousey, Karen; Taylor, Lauren; Moore, Barry; Patton, Declan; Moore, Zena; Avsar, Pinar
Abstract : Objective: The aim of this systematic review was to examine the associations and relationship between commonly cited risk factors and the pathology of pressure ulcer (PU) development. Method: Using systematic review methodology, original research studies, prospective design and human studies written in English were included. The search was conducted in March 2018, using Ovid, Ovid EMBASE and CINAHL databases. Data were extracted using a pre-designed extraction tool and all included studies were quality appraised using the evidence-based librarianship critical appraisal. Results: A total of 382 records were identified, of which five met the inclusion criteria. The studies were conducted between 1994 and 2017. Most studies were conducted in hospital and geriatric wards. The mean sample size was 96±145.7 participants. Ischaemia, recovery of blood flow and pathological impact of pressure and shear was mainly found as the cited risk factor and PU aetiology. Conclusion: This review systematically analysed five papers exploring the relationship between risk factors for PU development and aetiology. It identified many risk factors and underlying pathological mechanisms that interact in the development of PU including ischaemia, stress, recovery of blood flow, tissue hypoxia and the pathological impact of pressure and shear. There are several pathways in which these pathological mechanisms contribute to PU development and identifying these could establish potential ways of preventing or treating the development of PU for patients.